IMPLIKASI HUKUM ATAS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 25/PUU-XIV/2016 TERHADAP PEMBERANTASAN TINDAK PIDANA KORUPSI - Saputra, Dadin E.; Khalid, Afif (Syariah: Jurnal Hukum dan Pemikiran, 2018)
Abstract: There is an increase in corruption level in Indonesia, both in the total number of cases and in the total amount of financial losses suffered by the state. There are even more systematic corruption which present in all aspect of social life.The main problem formulation would be focusing on the consideration upon the decision of the panel of judges of the Constitutional Court in its decision Number 25/PUU-XIV/2016 and its legal implication towards law enforcement process and corruption eradication. The objective of this research is, first, to understand the legal consideration of the panel of judges of constitutional court in the decision Number 25/PUUXIV/2016. As for the second objective, the researcher would like to be cognizant of the legalimplication related with the law enforcement and corruption eradication process. In conducting the research, the researcher is using normative judicial research, with juridical approach as the method. This research is using qualitative method and in analytical-descriptive analysis. This research resulted in number of conclusions, per se, Constitutional Court decision Number 25/PUUXIV/2016 has created legal uncertainty related to the formulation of corruption; as corruption was material offense, whereof in the beginning was formal offense. Such circumstance obliges law enforcer to establish the ground on how much actual financial loss the state has suffered, not on potential financial loss. There is different, legally unrelated perspective in defining “could” as in “could inflict state financial loss or harm state economy” under criminal approach of Law on Corruption Eradication and under administrative approach of Law Number 30 Year 2004.Abstrak: pertimbangan hukum Majelis Hakim Mahkamah Konstitusi dalam Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016.Dan untuk mengetahui Implikasi hukum apa terkait dengan proses penegakan hukum dan pemberantasan tindak pidana korupsi. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif.Dalam penelitian ini peneliti menggunakan metode kualitatif dan diuraikan secara deskriptif analitis. Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016 melahirkan ketidakpastian hukum yaitu berkaitan dengan rumusan delik tindak pidana korupsi, dimana awalnya rumusan tindak pidana korupsi adalah delik formil menjadi delik materiil, sehingga penegak hukum harus dapat membuktikan berapa nilai kerugian keuangan negara atau perekonomian negara secara riil atau nyata (actual loss) bukan pada sudut pandang potensi nilai kerugian yang akan dialami (potential loss). Frasa kata “dapat” merugikan keuangan negara atau perekonomian negara antara pendekatan pidana sebagaimana dalam Undang-Undang Tindak Pidana Korupsi dengan pendekatan administratif sebagaimana dalam Undang-Undang Nomor 30 Tahun 2004 adalah 2 hal yang berbeda dan tidak mempunyai hubungan hukum.